2021
DOI: 10.1002/mrm.28822
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning‐based cardiac cine segmentation: Transfer learning application to 7T ultrahigh‐field MRI

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Pretraining DL models using public medical image datasets is a more effective technique. Ankenbrand et al illustrate this strategy by transferring weights from a DL model pretrained on a public medical image dataset to train their DL model for segmenting the heart on cardiac MRI data [ 41 ].…”
Section: Synthesismentioning
confidence: 99%
“…Pretraining DL models using public medical image datasets is a more effective technique. Ankenbrand et al illustrate this strategy by transferring weights from a DL model pretrained on a public medical image dataset to train their DL model for segmenting the heart on cardiac MRI data [ 41 ].…”
Section: Synthesismentioning
confidence: 99%
“…The herein used data were accessed on July 29, 2019. 24 As the Kaggle data are subject to inconsistencies, we performed a data curation as described by Ankenbrand et al 22 Detailed information and examples regarding data curation can be found in this online repository: https://github.com/chfc-cmi/ cmr-seg-tl#data-curat ion-and-conve rsion. The number of examinations in the repository within the 15% confidence set is higher than in this article.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The Kaggle data are a compilation of real, clinical data from multiple sites and as such, subject to inconsistencies within individual examinations. A data curation was performed as described by Ankenbrand et al, 22 to remove these inconsistencies as much as possible. More detailed information and examples regarding data curation can be found in this online repository: https://github.com/chfccmi/cmr-seg-tl#data-curat ion-and-conve rsion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNN and TL have been widely used in the prediction of medical conditions using different techniques (CT, MRI, panoramic images) -for example: identification of prostate cancer [12]; prediction of bladder cancer treatment response in CT [13]; detection of maxillary sinusitis on panoramic radiographs [14]; screening for osteoporosis in dental panoramic radiographs [15]; cardiac cine segmentation [16] and even COVID-19 detection from chest CT-scans [17].…”
Section: Introductionmentioning
confidence: 99%